Contamination of Food by Nitrosamines and the Associated Public Health Risks - Kumar, Arun HS (Biology, Engineering, Medicine and Science Reports)
The presence of N-Nitrosamines (N-NAs) in food poses a serious risk to public health, according to a recent scientific opinion by the European Food Safety Authority (EFSA).1,2 These genotoxic compounds, which induce liver tumours in rodents, are found in various food categories, with 'meat and meat products' being the main contributor to dietary exposure.1-3 The EFSA assessment revealed that the Margin of Exposure (MOE) for the 10 carcinogenic N-NAs (NDMA, NMEA, NDEA, NDPA, NDBA, NMA, NSAR, NMOR, NPIP, and NPYR) in food was highly likely to be less than 10,000 for all age groups, indicating a significant health concern.1-3 However, the assessment was limited by uncertainties due to censored data and lack of information on some food categories. This highlights the need for continued monitoring of N-NAs in food and the implementation of mitigation measures to protect public health.